Repeated measurements of Adaptive Force: Maximal holding capacity differs from other maximal strength parameters and preliminary characteristics for non-professional strength vs. endurance athletes - Schaefer, Laura V.; Carnarius, Friederike; Dech, Silas; Bittmann, Frank N. (Frontiers in Physiology, 2023)
The Adaptive Force (AF) reflects the neuromuscular capacity to adapt to external loads during holding muscle actions and is close to motions in real life and sports. The maximal isometric AF (AFisomax) was considered to be the most relevant parameter and was assumed to have major importance regarding injury mechanisms and the development of musculoskeletal pain. The aim of this study was to investigate the behavior of different torque parameters in the course of 30 repeated maximal AF trials. Besides, maximal holding vs. maximal pushing isometric muscle actions were compared. A side consideration was the behavior of torques in the course of repeated AF actions comparing strength vs. endurance athletes. Elbow flexors of n = 12 males (six strength/six endurance athletes, non-professional) were measured 30 times (120 s rest) by a pneumatic device. Maximal voluntary isometric contraction (MVIC) was measured pre and post. MVIC, AFisomax and AFmax (maximal torque of one AF measurement) were evaluated regarding different considerations and statistical tests. AFmax and AFisomax declined in the course of 30 trials (slope regression AFmax = – 0.323 ± 0.263; AFisomax = – 0.45 ± 0.45). The decline from start to end amounted averagely – 12.8 ± 8.3% (p < 0.001) for AFmax and – 25.41 ± 26.40% (p < 0.001) for AFisomax. AF parameters declined more in strength vs. endurance athletes. Thereby, strength athletes showed a rather stable decline for AFmax and a plateau formation for AFisomax after 15 trials. In contrast, endurance athletes reduced their AFmax especially after the first five trials and remained on a rather similar level for AFisomax. The maximum of AFisomax of all 30 trials amounted 67.67 ± 13.60% of MVIC (p < 0.001, n = 12), supporting the hypothesis of two types of isometric muscle action (holding vs. pushing). The findings provide first data on the behavior of torque parameters after repeated isometric-eccentric actions and revealed further insights into neuromuscular control strategies. Additionally, they highlight the importance to investigate AF parameters in athletes reasoned by the different behavior compared to MVIC. This is assumed to be especially relevant regarding injury mechanisms.